Effect of Steel Braces on Progressive Collapse Using Applied Element Method - Hafez, Laith M.Abd El; Genes, Mehmet Cemal (Springer Science and Business Media Deutschland GmbH, 2024)
It is widely common to see terrorist attacks nowadays happening around the globe. In this study bracing effect on progressive collapse will be discussed. To start with, this study will analyze the collapse mechanism, due to explosive load on an average height building, which mimics important buildings like government buildings, ministries, hospitals, etc. Explosive loads are the loads coming from the explosion of a certain amount of TNT with respect to the standoff distance from the explosion. So, any terrorist attacks will target the columns at the ground floor to maximize the damage imposed on the structure achieving the highest number of casualties. As a result, this study covers the load transfer mechanism to prevent a progressive collapse in case of column loss scenario, which occurs in a terrorist attacks or earthquakes. Moreover, this study discusses multiple technologies to counteract and resist column removal. First of all, constructing tensile steel braces at one of the stories which can be used to transfer the load coming from upper stories to ground floor. Secondly, this study will discuss the effect of column removal location on the total deflection of the structure and the axial loads imposed on the nearby columns. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.
15th International Congress on Advances in Civil Engineering, ACE 2023 -- 2023-09-06 through 2023-09-08 -- Famagusta -- 312069
Keywords: Applied Element Method (AEM); Braces; Extreme Loading on Structures (ELS); Progressive Collapse